Transfer of Knowledge from First-Year English Writing Classes To Writing in the Disciplines: Case Studies of Writing across the Curriculum - Abdelhak, NEMOUCHI; Nesrine, HAMANI (Sciences humaines, 2016)
The present study sheds light on the advantages of the program designed to teach writing across the curriculum and tries to, as well, determine what features students should transfer while writing different assignments across different disciplines. The study is based on an analysis of a questionnaire administered to English teachers of different subjects at the Department of English Letters and Language, University Mentouri Bros, Constantine, Algeria. The selected questions try to examine first the students’ writing performance, second if the writing rules are reflected in the students’ assignments, or not, and finally how teachers define the term writing across the curriculum Key words: Writing across the curriculum, writing rules, transfer, disciplines, and subjects. هذه الدراسة تسلط الضوء على مزايا برنامج مصمم لتعليم الكتابة عبر المناهج الدراسية ويحاول، وكذلك، تحديد ما يتميز ينبغي نقل الطلاب أثناء كتابة المهام المختلفة عبر مختلف التخصصات. وتعتمد الدراسة على تحليل استبيان تدار على مدرسي اللغة الإنجليزية من الموضوعات المختلفة في قسم اللغة الإنجليزية الآداب واللغة، جامعة منتوري بروس، قسنطينة، الجزائر. الأسئلة المختارة في محاولة لدراسة أولا "أداء الكتابة، والثانية إذا تنعكس قواعد الكتابة في الطلاب الطلاب الواجبات، أو لا، وأخيرا كيف المدرسين تحديد المدى الكتابة عبر المناهج الدراسية الكلمات المفتاحية: الكتابة عبر المناهج الدراسية، وكتابة القواعد ونقلها والتخصصات، والموضوعات.